Pengaruh Post Welding Heat Treatment (PWHT) Pada Friction Stir Welding Pada Material Aluminium AA5052/6061 Terhadap Sifat Mekanik dan Struktur Mikro - Wahyu Ari Putranto; Khaeroman Khaeroman; Akhmad Nuriyanis; Arif Rakhman Suharso; Evi Sirait (P3M Politeknik Negeri Cilacap, 2026)
The development of technology in the maritime sector is very rapid in the manufacture of aluminum ships. Friction Stir Welding (FSW) is a green technology in the metal joining process. Post Welding Heat Treatment (PWHT) is one way to increase the loss of strength of the material connection after the FSW process. The purpose of this study was to determine the effect of FSW results before and after PWHT. Aluminum alloy (AA) series 5052 and 6061 were used as research materials because they are resistant to seawater. FSW parameters were spindle speed 1500 rpm (clockwise), travel speed 30 mm/min, tool depth 0.2 mm, and tool tilt 1o. PWHT parameters were heating the FSW material in a furnace to a temperature of 550°C (10, 30 minutes), water quenching, and artificial aging to a temperature of 180°C for 7 hours. The material was characterized by tensile testing, hardness, and micrography. The highest tensile strength and hardness values were 216 MPa and 68 HV, the smallest and uniform grain size in the weld zone and base metal areas were obtained at PWHT parameters of 30 minutes.